Features and Principles of Formation of Marketing Strategies in the Activity of Agricultural Enterprises of Ukraine - Byvsheva, L.; Kondratenko, O.; Kovalenchenko, A. (Економічний вісник Донбасу, 2019)
The article defines that the marketing strategy is a general philosophy of doing business in the context of globalization and involves the development of strategic directions and methodological tools for achieving long-term competitive advantages and the possibility of timely adaptation of business entities to the dynamic changes of macro and microenvironmental factors, contributing to the needs and environment. consumers according to social values. The marketing strategy of the company is formed on the basis of the basic concept of its development and takes into account resources and opportunities, the state and peculiarities of competition, demand trends, conditions of marketing environment and internal factors that are interconnected and observed chain reaction, which is displayed on the change in the final result. The order of formation and realization of the marketing strategy of the enterprises in the agro-industrial market is presented. The importance of taking into account strategic market risks has been updated. The principles of marketing strategy formation are substantially different from the principles of formation of the overall development strategy and follow from the very essence of marketing. It is proved that in formulating a marketing strategy of an agricultural enterprise, it is necessary to coordinate its potential capabilities in terms of meeting the requirements of the end consumers regarding the range, quality and price of agricultural products, to take into account the maximum use of their competitive advantages and weak positions of competitors, to substantiate the strategies of the main elements of the marketing complex: distribution and promotion.